Contrasts in the governance structures in the transborder regions Andaluzia – Algarve - Dominguez, José Andres (2014)
The goal of this work is to detect the basic characteristics of the development of the southern border between Spain and Portugal. This trans-border area is described and analyzed comparing the region of Algarve, in Portugal and the region of the County, in Huelva, Spain. The method used 15 quantitative indicators, desegregated at municipal level, obtained from different official sources and applied to 30 municipalities. The analysis includes multivariate statistic methods. The conclusions show that those indicators related to national governance systems are of utmost importance in the cluster classification. Furthermore, those municipalities with higher development levels are also less sustainable from the environmental point of view – this is probably due to the fact that tourism supports the fragile socio-economic systems in many of such regions. Significantly, the clustering tendencies show that the Portuguese municipalities are tourism oriented (or less tourism oriented) and the Spanish ones are agribusiness (or less agribusiness oriented). Lastly, such geographic structures seem to have its roots in long term paths of development.